Chemical Mechanical Polishing Slurry
By using flower-shaped δ-MnO2 nanoparticles as catalyst aid, an efficient chemical mechanical polishing liquid was prepared, which solved the problem of low material removal rate during silicon carbide wafer polishing, and achieved efficient and low-cost polishing effect.
Patent Information
- Application Number
- CN202411314487.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-09-20
AI Technical Summary
In the chemical mechanical polishing process of silicon carbide wafers, due to the high hardness and strong chemical inertia of the material, the material removal rate, long processing time and high cost, seriously restricting its industrial application.
A highly efficient chemical mechanical polishing liquid was prepared by mixing it with oxidizing agent, abrasive particles and pH adjusting agent. The nanoparticles have a high specific surface area, rich pore structure and high concentration of oxygen vacancies, which can significantly increase the polishing rate of silicon carbide.
It significantly improves the polishing rate of silicon carbide wafers, the polished wafer has high flatness and no scratches, reducing the polishing cost, and the process is simple, safe and free of heavy metal pollution, making it suitable for industrial applications.
Smart Images

Figure CN118813141B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano material and silicon carbide polishing, in particular to a chemical mechanical polishing liquid. Background Art
[0002] Single crystal silicon carbide (SiC) is a typical representative of the third generation of semiconductor materials, with wide band gap, high critical breakdown electric field, high thermal conductivity, high carrier saturation migration velocity, low relative dielectric constant, high temperature resistance and radiation resistance. Silicon carbide substrates are divided into conductive and semi-insulating types according to their resistivity. After epitaxial deposition of silicon carbide and gallium nitride, they are used to make power devices and radio frequency devices. Silicon carbide power devices have been widely used in the fields of power and electronics, such as electric vehicle inverters and charging piles for new energy vehicles, photovoltaic inverters in the photovoltaic industry, and power semiconductor devices in the field of rail transportation, such as traction converters, auxiliary converters, main and auxiliary integrated converters, power electronic transformers, power chargers, etc. Radio frequency devices are the core components of wireless communication, including radio frequency switches, LNAs, power amplifiers and filters. Among them, the power amplifier directly affects the transmission distance and signal quality of base station signals. Silicon-based LDMOS devices have been used for many years, but they are mainly used in low-frequency fields below 4GHz. The high frequency, high speed and high power characteristics of 5G communications also put forward higher requirements on the performance of power amplifiers. Silicon carbide-based gallium nitride has the advantages of good thermal conductivity, high frequency, high power, etc., and has become the core RF device of 5G communication systems, new generation active phased array radars and other systems, and is expected to replace silicon-based LDMOS.
[0003] However, the quality and precision of SiC wafer surface processing directly affect the quality of epitaxial film and the performance of its devices. Therefore, in its application, the wafer surface is required to be ultra-smooth, defect-free, and damage-free, with a surface roughness value of less than nanometer level. Chemical-Mechanical Polishing (CMP) is the mainstream polishing technology for semiconductor wafers, which can achieve the flattening of single crystal silicon, gallium arsenide, silicon carbide and other substrate materials. Chemical mechanical polishing is to rotate the wafer relative to the polishing pad under a certain downward pressure and the presence of polishing liquid (containing abrasives and chemical reagents), and use the mechanical grinding of abrasives and the corrosion of chemical reagents to complete the material removal on the surface of the workpiece and obtain a smooth and flat surface. However, the hardness of silicon carbide material is extremely high and its chemical inertness is strong. The mechanical grinding and chemical corrosion rates are extremely low, resulting in a low material removal rate, long wafer processing time and high cost, which seriously restricts the industrial application of silicon carbide wafers. Therefore, it is necessary to develop an efficient silicon carbide wafer polishing liquid to increase the wafer removal rate and reduce the polishing cost. In recent years, a variety of new polishing technologies have been applied to the polishing of silicon carbide wafers, such as catalyst-assisted chemical mechanical polishing, electrochemical mechanical polishing (ECMP), plasma-assisted polishing (PAP) and photocatalytic chemical mechanical polishing (PCMP), etc. They use different methods to accelerate the oxidation rate of silicon carbide wafers. Among them, catalyst-assisted chemical mechanical polishing has low cost and strong applicability, and has the most industrial application prospects, and its core lies in the development of high-performance catalysts. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a chemical mechanical polishing liquid in view of the deficiencies in the above-mentioned prior art.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: In the first aspect of the present invention, a flower-shaped δ-MnO2 nanoparticle is provided, which is prepared by the following method:
[0006] S1, using an organic compound as a reducing agent and dissolving it in deionized water to obtain solution A;
[0007] S2, dissolving permanganate (oxidant) in deionized water to obtain solution B;
[0008] S3, mixing solution A and solution B, reacting to obtain flower-shaped δ-MnO2 nanoparticles;
[0009] The flower-shaped δ-MnO2 nanoparticles are used as a catalyst to prepare a chemical mechanical polishing liquid. The flower-shaped δ-MnO2 nanoparticles are produced by the redox reaction of the reducing agent in liquid A and the oxidizing agent in liquid B. The flower-shaped MnO2 has a flake-like morphology and a high specific surface area (greater than 100 m 2 / g) and rich pore structure (high pore volume: greater than 0.2 cm 3 / g and rich mesopores: the pore size of the mesopores is greater than 10 nm) and a high concentration of oxygen vacancies. As a catalytic aid, it can promote the catalytic oxidation of various wafer materials (such as silicon carbide wafers), and can thus be well used in the preparation of chemical mechanical polishing solutions.
[0010] Preferably, the organic compound is selected from one or more of alcohols, aldehydes, and organic acids. More preferably, the organic compound is selected from one or more of methanol, ethanol, propanol, isopropanol, sec-butanol, polyethylene glycol, formaldehyde, acetaldehyde, propionaldehyde, formic acid, acetic acid, propionic acid, and oxalic acid.
[0011] Preferably, the permanganate is selected from one or more of potassium permanganate, sodium permanganate and calcium permanganate.
[0012] Preferably, the molar concentration of the organic compound in solution A is 0.01 to 18.0 mol / L, and the molar concentration of the permanganate in solution B is 0.01 to 2.0 mol / L;
[0013] In step S3, solution A and solution B are added in a molar ratio of organic compound to permanganate of 0.2 to 5.0:1.
[0014] Preferably, in step S3, the reaction time is 0.5-48 h, the reaction temperature is 20° C.-100° C., and the reaction pH is 1.0-14.0.
[0015] Preferably, the organic compound in solution A is ethanol with a concentration of 2.84 mol / L; the permanganate in solution B is potassium permanganate with a concentration of 0.40 mol / L;
[0016] In step S3, solution A and solution B are added in a molar ratio of organic compound to permanganate of 1.5:1;
[0017] The reaction time in step S3 is 24 h, the reaction temperature is 20° C., and the reaction pH is 10.
[0018] The second aspect of the present invention provides an application of the flower-shaped δ-MnO2 nanoparticles as described above in chemical mechanical polishing, and the application method is: the flower-shaped δ-MnO2 nanoparticles as described above are used as a catalytic aid, and are mixed with raw materials including an oxidant, abrasives, and a pH adjuster to prepare a chemical mechanical polishing liquid, and then the chemical mechanical polishing liquid is used for chemical mechanical polishing.
[0019] A third aspect of the present invention provides a chemical mechanical polishing solution comprising the following components:
[0020] 1.0% to 10.0wt% of flower-shaped delta-MnO2 nanoparticles, 1.0% to 10.0wt% of abrasive particles, 0.1 to 20.0% of an oxidant, and a pH regulator in an amount such that the pH value of the chemical mechanical polishing solution reaches 1.0 to 14.0.
[0021] Preferably, the oxidant is selected from one or more of potassium permanganate, potassium manganate, hydrogen peroxide, persulfate, cerium ammonium nitrate, periodic acid, chlorate, bromate, ferrate, permanganate, chromate, and perchromate.
[0022] Preferably, the abrasive grains are selected from one or more of α-aluminum oxide, silicon dioxide, zirconium dioxide, titanium dioxide, silicon carbide, boron carbide, silicon nitride and diamond.
[0023] Preferably, the pH regulator is selected from one or more of phosphoric acid, hydrogen phosphate, nitric acid, sulfuric acid, potassium hydroxide, sodium hydroxide, triethanolamine, oxalic acid, and amino acids.
[0024] Preferably, in the chemical mechanical polishing liquid:
[0025] The concentration of δ-MnO2 nanoparticles 1.0%~10.0 wt% is 1.5 wt%; the abrasive is α-alumina abrasive, and the concentration is 2.0 wt%; the oxidant is potassium permanganate, and the concentration is 2.0 wt%; the pH value of the chemical mechanical polishing solution is 8.5.
[0026] Preferably, the application objects of the chemical mechanical polishing liquid include but are not limited to amorphous silicon carbide, silicon nitride, sapphire, metal, diamond, aluminum oxide, gallium nitride, gallium arsenide, single crystal silicon and polycrystalline silicon.
[0027] The beneficial effects of the present invention are:
[0028] The present invention provides flower-shaped δ-MnO2 nanoparticles, application of the nanoparticles in chemical mechanical polishing, and chemical mechanical polishing liquid based on the nanoparticles. The flower-shaped δ-MnO2 nanoparticles prepared by the present invention have rich pore structures, high specific surface area, high concentrations of oxygen vacancies and active sites, and can better catalyze the oxidation process of silicon carbide wafers. Compared with traditional polishing liquids, the flower-shaped δ-MnO2 nanoparticles can significantly improve the polishing rate of silicon carbide as a chemical mechanical polishing catalyst aid, and the polished wafers have high flatness and are free of scratches.
[0029] The present invention uses cheap chemical raw materials to prepare flower-shaped δ-MnO2 nanoparticles. The synthesis steps are simple and safe, no separation and purification are required, the equipment cost and operation cost are low, and there is no heavy metal environmental pollution and volatility problem. It is easy to store and transport for a long time, which is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The XRD patterns of several catalyst promoters in the examples and comparative examples are shown;
[0031] Figure 2 The following are scanning electron microscope photos of several catalyst promoters in the examples and comparative examples;
[0032] Figure 3 Zeta potential and particle size distribution of several catalyst promoters in the examples and comparative examples;
[0033] Figure 4 The nitrogen adsorption-desorption isotherms (a) and pore size distribution (b) of several catalyst promoters in the examples and comparative examples;
[0034] Figure 5 The XPS spectra (X-ray photoelectron spectroscopy) of several catalyst promoters in the examples and comparative examples are shown. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.
[0036] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.
[0037] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0038] Example 1
[0039] A flower-shaped delta-MnO2 nanoparticle is prepared by the following method:
[0040] S1, take 6.15 g of anhydrous ethanol and mix it with 47.0 g of deionized water to obtain 2.84 mol / L ethanol solution A;
[0041] S2, mixing 14.06 g potassium permanganate with 220.0 g deionized water to obtain a potassium permanganate solution B with a concentration of 0.33 mol / L;
[0042] S3, quickly mix liquid A and liquid B and stir the mixture at room temperature for 24 hours to obtain 280.0 g of a suspension containing 10 g of flower-like δ-MnO2 nanoparticles; wherein the pH of the reaction solution is 6.5. The prepared flower-like δ-MnO2 nanoparticles are recorded as EtOH-MnO2.
[0043] A chemical mechanical polishing liquid, the preparation method of which is as follows:
[0044] 20.0 g of α-alumina abrasive and 20.0 g of potassium permanganate were added to the above prepared 280.0 g suspension containing 10 g of flower-shaped δ-MnO2 nanoparticles, and then 680.0 g of deionized water was added to finally obtain a chemical mechanical polishing solution with a total weight of 1000 g.
[0045] The final chemical mechanical polishing liquid contains: 2.0 wt% potassium permanganate (oxidant), 2.0 wt% α-alumina abrasive and 1.0 wt% flower-shaped δ-MnO2 nanoparticles (catalytic aid); the pH of the polishing liquid is adjusted to 8.5 by adding dilute nitric acid or dilute potassium hydroxide solution, and then polishing is applied.
[0046] In all embodiments and comparative examples, the polishing application object and related process parameters are the same, specifically as follows: the polishing application object is a 4-inch silicon carbide wafer (polished silicon surface), and the polishing condition parameters are shown in Table 1:
[0047] Table 1 Polishing condition parameters
[0048] Polishing conditions parameter Polishing pad Suba 800 Polishing time 60 min Footplate pressure <![CDATA[280 g / cm 2 ]]> Polishing pad speed 55 rpm Polishing liquid flow rate 270 mL / min
[0049] The calculation of the removal rate (MRR) during polishing is as follows:
[0050]
[0051] Where Δm (g) is the weight loss of the silicon carbide wafer during the polishing process, and ρ is the density of silicon carbide (ρ = 3.2 g / cm 3 ), t is the polishing time (t = 1 h), and r is the radius of the SiC wafer (r = 10.16 cm).
[0052] The polishing liquid in Example 1 has a removal rate (MRR) of 1.26 μm / h for the silicon surface-silicon carbide wafer.
[0053] Example 2
[0054] This example is basically the same as Example 1, except that the reducing agent in step S1 of this example is replaced by oxalic acid (oxalic acid) of equal molar concentration instead of ethanol. The flower-shaped δ-MnO2 nanoparticles prepared in this example are denoted as OA-MnO2.
[0055] The polishing liquid prepared in this example has a removal rate (MRR) of 1.01 μm / h for silicon surface-silicon carbide wafer.
[0056] Comparative Example 1
[0057] This example is basically the same as Example 1, except that the polishing liquid in this example does not contain flower-shaped δ-MnO2 nanoparticles, and its preparation method is as follows: 960.0 g of deionized water is prepared, 20.0 g of α-alumina abrasive particles and 20.0 g of potassium permanganate are added, and finally a polishing liquid with a total weight of 1000 g is obtained. Dilute nitric acid or dilute potassium hydroxide solution is added to adjust the pH of the polishing liquid to 8.5, and then polishing is applied.
[0058] The polishing liquid prepared in this example has a removal rate (MRR) of 0.96 μm / h for silicon surface-silicon carbide wafer.
[0059] Comparative Example 2
[0060] This example is basically the same as Example 1, except that commercially available γ-MnO2 (Aladdin reagent, chemically pure) is used to replace the flower-shaped δ-MnO2 nanoparticles in Example 1.
[0061] The polishing liquid prepared in this example has a removal rate (MRR) of 0.83 μm / h for silicon surface-silicon carbide wafer.
[0062] Example 3
[0063] In order to explore the effect of the catalyst on the polishing removal rate, the following example uses the same method as Example 1 to prepare polishing liquids containing flower-shaped δ-MnO2 nanoparticles of different concentrations (0.5wt%, 1.5wt%, 2.0wt%), and polishing applications are performed to test the polishing removal rate. The test results of Examples 1-3 and Comparative Examples 1-2 are summarized in Table 2 below:
[0064] Table 2 Effect of catalyst additives on removal rate
[0065] Catalytic additives Removal rate (μm / h) Increase percentage No catalyst additive (Comparative Example 1) 0.96 NA <![CDATA[1.0% commercial γ-MnO2 (Comparative Example 2)]]> 0.98 +2.1% <![CDATA[1.0% OA-MnO2 (Example 2)]]> 1.01 +5.2% <![CDATA[0.5% Flower-like δ-MnO2 (Example 3)]]> 1.15 +19.60% <![CDATA[1.0% Flower-like δ-MnO2 (Example 1)]]> 1.18 +22.40% <![CDATA[1.5% Flower-like δ-MnO2 (Example 3)]]> 1.30 +35.20% <![CDATA[2.0% Flower-like δ-MnO2 (Example 3)]]> 1.11 +14.80%
[0066] Table 2 compares the effects of different types of catalysts and catalyst concentrations on the removal rate. It can be seen from Table 2 that when using MnO2 catalyst, the polishing rate is improved to a certain extent compared with Comparative Example 1 (without catalyst), among which the flower-shaped δ-MnO2 catalyst has the highest removal rate, which can be increased by 31.3% (at a concentration of 1.5%). OA-MnO2 can be increased by 5.2%, while commercial γ-MnO2 can only be increased by 2.1%. For flower-shaped manganese dioxide, the removal rate increases with the increase of its concentration, reaching a relative maximum at 1.5%, and then the removal rate decreases, but it is still significantly higher than the removal rate of γ-MnO2 and without catalyst.
[0067] Example 4 Performance Characterization and Testing of Several Catalytic Aids in Examples and Comparative Examples
[0068] 1. Reference Figure 1 , are the XRD patterns of several catalyst promoters in the embodiments and comparative examples, Figure 1 It can be seen that the standard XRD patterns of commercial γ-MnO2 are consistent with those of γ-MnO2, and there is no impurity phase. The standard XRD patterns of flower-like δ-MnO2 (EtOH-MnO2) and OA-MnO2 are consistent with those of δ-MnO2, indicating that their crystal structure is δ-MnO2. The diffraction peaks of the XRD pattern of the flower-like δ-MnO2 catalyst are broad and weak, indicating that its crystallinity is low and there are a large number of defects; from the perspective of catalytic oxidation, the presence of these defects can serve as active sites to promote the oxidation of silicon carbide wafers.
[0069] 2. Reference Figure 2 , are scanning electron microscope photos of several catalytic promoters in the examples and comparative examples: (a) flower-shaped δ-MnO2 (EtOH-MnO2), (b) OA-MnO2, (c) commercial γ-MnO2. Figure 3 The zeta potential and particle size distribution of several catalyst promoters in the examples and comparative examples are shown.
[0070] It can be seen that γ-MnO2 is composed of fine rod-like structures with an average size of less than 50 nm, and the average particle size is 283.3 nm. The flower-like δ-MnO2 particles (EtOH-MnO2) are nanoflower structures composed of nanosheets. The thickness of the nanosheets is less than 40 nanometers, and the average particle size of the nanoflowers is 273 nm. The morphology of OA-MnO2 is similar to that of EtOH-MnO2, but the particle size is larger, about 460 nm. The size and morphology of the particles are important parameters of catalytic promoters. Small particles often have a high surface / volume ratio and a large specific surface area, thus providing more active sites on the surface. These active sites are conducive to the adsorption and conversion of reactants and intermediates, and have a promoting effect on the reaction rate. The nanoflower morphology composed of nanosheets can also effectively promote the reaction. The flower-like structure has abundant macropores and mesopores, which is conducive to the mass transfer and diffusion of reactants and products; the crystals with thin sheet structures have an extremely high surface-to-volume ratio, which greatly reduces the diffusion resistance of reactants in the internal pores of the crystals, which is conducive to the improvement of the reaction rate.
[0071] Depend on Figure 3 It can be seen from the Zeta potential that when pH is 8, the surfaces of the three catalyst aids are all negatively charged, and the Si surface of the silicon carbide crystal surface is also negatively charged, so the catalyst aid will not accumulate on the crystal surface, thereby not affecting the catalytic performance of the catalyst aid. The potential of the two catalyst aids synthesized by the present invention is nearly -30mV, and has good dispersion stability. The uniform dispersion of abrasive particles in the polishing liquid not only improves the polishing rate, but also avoids surface scratches caused by particle agglomeration.
[0072] 3. Reference Figure 4 , are nitrogen adsorption-desorption isotherms (a) and pore size distribution (b) of several catalyst promoters in the examples and comparative examples. Table 3 below shows the BET specific surface area, pore volume and pore size measurement data of several catalyst promoters.
[0073] Table 3 BET specific surface area, pore volume and pore size of MnO2 catalyst promoter
[0074] sample <![CDATA[BET specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Pore size (nm) <![CDATA[γ-MnO2]]> 36.3 0.05 3.65 <![CDATA[EtOH-MnO2]]> 136.3 0.51 3.62 <![CDATA[OA-MnO2]]> 42.0 0.13 3.92
[0075] Depend on Figure 4 It can be seen from the nitrogen adsorption isotherms of the three MnO2 samples that the nitrogen adsorption isotherms have hysteresis loops, indicating the existence of mesoporous channels. The BET specific surface area of commercial γ-MnO2 is 36.3 m 2 / g, and the pore volume is small, only 0.05 cm 3 / g. The EtOH-MnO2 and OA-MnO2 prepared by the present invention have high specific surface area and pore volume. The BET specific surface area of OA-MnO2 is 42.0m 2 / g, pore volume is 0.13 cm 3 / g. The specific surface area of EtOH-MnO2 ET is 137.3 m 2 / g, pore volume is 0.51 cm 3 / g. The pore size distribution calculated based on the BJH desorption branch shows that all the above samples have mesopores with pore sizes ranging from 3.6 to 4.0 nm.
[0076] According to traditional catalysis and reaction engineering principles, high specific surface area can provide more active sites, which is conducive to the adsorption of reactants and intermediates on the surface of the catalyst promoter, and has a promoting effect on the reaction. The rich pore structure, especially the presence of mesopores, is conducive to the diffusion of reactants, relieves mass transfer constraints, and promotes reaction kinetics. Therefore, the catalyst promoter with high specific surface area and rich mesopores has a great promoting effect on the oxidation reaction and material removal rate of silicon carbide. Among them, the flower-shaped EtOH-MnO2 synthesized by the present invention has the highest specific surface area and porosity, the strongest promoting effect on the reaction, and the highest polishing rate.
[0077] 4. Reference Figure 5 , are XPS spectra (X-ray photoelectron spectroscopy) of several catalyst promoters in the examples and comparative examples: (a) XPS full spectrum, (b) O1s spectrum, (c) Mn3S spectrum, (d) Mn 2P spectrum, (e) O latt / O ads Ratio (ratio of lattice oxygen to adsorbed oxygen), (f) Mn 3+ / Mn 4+ Proportion.
[0078] The analysis results are shown in Table 4.
[0079] Table 4. XPS data analysis of MnO2 catalyst promoter
[0080] sample <![CDATA[Lattice oxygen (O lat ), Mn-O-Mn]]> <![CDATA[Adsorbed oxygen (O ads )Mn-O-H]]> <![CDATA[Mn 3+ / Mn 4+ ]]> AOS <![CDATA[γ-MnO2]]> 65.8% 34.2% 0.52 3.57 <![CDATA[EtOH-MnO2]]> 47.0% 53.0% 1.13 3.28 <![CDATA[OA-MnO2]]> 48.4% 51.6% 1.07 3.52
[0081] According to the test results, compared with commercial γ-MnO2, the δ-MnO2 synthesized by the present invention contains more Mn(III) (equivalent to a lower average oxidation state) and more oxygen vacancies (oxygen vacancies are adsorbed oxygen in Table 4. Since the sample is in contact with air, all the oxygen vacancies on the surface are occupied by oxygen in the air. Therefore, adsorbed oxygen is actually oxygen vacancies). According to traditional catalytic theory, oxygen vacancies in catalytic promoters can promote the activation and diffusion of active oxygen and provide active sites and adsorption sites, thereby accelerating various catalytic oxidation processes. Adsorbed oxygen O of OA-MnO2 and EtOH-MnO2 adsThe ratios are 51.6% and 53.0%, respectively, which are significantly higher than 34.2% of γ-MnO2. Adsorbed oxygen is oxygen vacancies, because oxygen in the air will directly react with oxygen vacancies in the sample to form adsorbed oxygen. The presence of Mn (III) and Mn (II) is also directly related to the formation of oxygen vacancies, because removing an O atom from a MnO2 crystal is equivalent to replacing a Mn 4+ Reduction to Mn 2+ , or two Mn 4+ Reduced to two Mn 3+ . Compared with the commercial γ-MnO2 sample (AOS=3.57), the AOS (average oxidation state) of OA-MnO2 and EtOH-MnO2 samples is lower. The lower AOS indicates that the Mn (IV) part is reduced and the Mn (III) species are more, which is directly related to the formation of oxygen vacancies. Due to the formation of oxygen vacancies, the Mn (IV) in the MnO2 framework is partially reduced to Mn (III). Studies have shown that the coexistence of Mn of different valence states (especially Mn (III)) in the MnO2 framework can effectively improve its oxidation activity.
[0082] In summary, we can draw the following conclusions:
[0083] 1. The polishing effect of δ-MnO2 nanoparticle catalyst additive with flower-like morphology is the best.
[0084] 2. Due to the presence of a large number of surface defects, small particle size and flower-like structure composed of thin flaky crystals on the surface of the catalyst, it has a high surface area and abundant active sites, which can effectively promote the oxidation of silicon carbide wafers, thereby increasing the material removal rate.
[0085] 3. The mesoporous structure in the catalyst can promote the diffusion of reactants and intermediates, relieve mass transfer constraints, and promote reaction kinetics on the wafer surface.
[0086] 4. The synthesized catalyst promoter has abundant oxygen vacancies, which can promote the activation and diffusion of oxygen and the oxidation of the wafer surface. At the same time, oxygen vacancies can provide active sites and adsorption sites, which are beneficial to the adsorption of reactants and intermediates and promote the oxidation of silicon carbide wafers.
[0087] Example 5 Effect of reaction time on polishing rate
[0088] This example is basically the same as Example 1, the only difference is the reaction time in step S3. Example 1 is 24 h, and this example tests the polishing rate at 0.02 h, 2 h, and 12 h respectively. The composition and polishing conditions of the prepared polishing liquid are the same as those in Example 1. The polishing results at different reaction times are shown in Table 5:
[0089] Table 5 Effect of reaction time on polishing rate
[0090] Reaction time MRR 0.02 h 1.12 μm / h 2 h 1.21 μm / h 12 h 1.23 μm / h 24 h 1.30 μm / h 36 h 1.20 μm / h
[0091] It can be seen from the results in Table 5 that when the reaction time is different, the polishing rate is improved to a certain extent compared with the comparative example 1 (without catalyst), among which the removal rate is the highest when the reaction time is 24 h.
[0092] Example 6 Effect of reaction temperature on polishing rate
[0093] This example is basically the same as Example 1, the only difference is the reaction temperature in step S3. Example 1 is 20°C, and this example tests the polishing rate at 40°C, 60°C, and 80°C. The composition and polishing conditions of the prepared polishing liquid are the same as those in Example 1. The polishing results at different reaction temperatures are shown in Table 6:
[0094] Table 6 Effect of reaction temperature on polishing rate
[0095] Reaction temperature MRR 20 ℃ 1.30 μm / h 40 ℃ 1.23 μm / h 60 ℃ 1.18 μm / h 80 ℃ 1.13 μm / h
[0096] It can be seen from the results in Table 6 that when the reaction temperature is different, the polishing rate is improved to a certain extent compared with the comparative example 1 (without catalyst), among which the removal rate is the highest when the reaction temperature is 20 °C.
[0097] Example 7 Effect of pH of Solution Reaction on Polishing Rate
[0098] This example is basically the same as Example 1, the only difference is the pH value of the reaction solution in step S3. The pH of the reaction solution in step 3 of Example 1 is 6.5. This example tests the polishing rate at pH 8.5 and 10 of the reaction solution, respectively. The composition and polishing conditions of the prepared polishing solution are the same as those of Example 1. The polishing results at different reaction solution pH are shown in Table 7:
[0099] Table 7 Effect of pH of solution reaction on polishing rate
[0100] Solution reaction pH MRR 6.5 1.30 μm / h 8.5 1.28 μm / h 10 1.32 μm / h
[0101] It can be seen from the results in Table 7 that when the pH of the solution reaction is different, the polishing rate is improved to a certain extent compared with Comparative Example 1 (without catalyst additive), among which the removal rate is the highest when the pH of the solution reaction is 10, but it is basically within the range of experimental error.
[0102] Example 8 Effect of ethanol solution concentration on polishing rate
[0103] This example is basically the same as Example 1, the only difference is the ethanol concentration in the ethanol solution in step S1. The ethanol concentration in the ethanol solution in Example 1 is 2.84 mol / L. This example tests the polishing rate at ethanol solution concentrations of 17.2 mol / L and 1.42 mol / L, respectively. The composition and polishing conditions of the prepared polishing liquid are the same as those in Example 1. The polishing results at different ethanol solution concentrations are shown in Table 8:
[0104] Table 8 Effect of ethanol solution concentration on polishing rate
[0105] Ethanol solution concentration MRR 1.42 mol / L 1.08 μm / h 2.84 mol / L 1.30 μm / h 17.2 mol / L 1.16 μm / h
[0106] It can be seen from the results in Table 8 that when the concentration of the ethanol solution is different, the polishing rate is improved to a certain extent compared with the comparative example 1 (without a catalyst additive), among which the removal rate is the highest when the concentration of the ethanol solution is 2.84 mol / L.
[0107] Example 9 Effect of potassium permanganate solution concentration on polishing rate
[0108] This example is basically the same as Example 1, the only difference is the concentration of potassium permanganate in the potassium permanganate solution in step S2. The concentration of potassium permanganate in Example 1 is 0.40 mol / L, and the concentration of potassium permanganate in this example is 0.80 mol / L. The composition and polishing conditions of the prepared polishing liquid are the same as those in Example 1. The polishing results at different concentrations of potassium permanganate solution are shown in Table 9:
[0109] Table 9 Effect of potassium permanganate solution concentration on polishing rate
[0110] Potassium permanganate solution concentration MRR 0.40 mol / L 1.30 μm / h 0.80 mol / L 1.25 μm / h
[0111] It can be seen from the results in Table 9 that when the concentration of potassium permanganate solution is different, the polishing rate is improved to a certain extent compared with Comparative Example 1 (without catalyst additive), among which the removal rate is the highest when the concentration of potassium permanganate solution is 0.40 mol / L.
[0112] Example 10 Effect of reactant ratio on polishing rate
[0113] This example is basically the same as Example 1, the only difference is the molar ratio of the reactants in step S3. The molar ratio of ethanol to potassium permanganate in step S3 of Example 1 is 1.5. This example tests the polishing rates at ratios of 0.75, 1.875, and 2.25, respectively. The composition and polishing conditions of the prepared polishing liquid are the same as those of Example 1. The polishing results at different molar ratios of the reactants are shown in Table 10:
[0114] Table 10 Effect of reactant ratio on polishing rate
[0115] Molar ratio of reactants MRR 0.75 1.15 μm / h 1.5 1.30 μm / h 1.875 1.20 μm / h 2.25 1.13 μm / h
[0116] It can be seen from the results in Table 10 that when the molar ratio of the reactants is different, the polishing rate is improved to a certain extent compared with the comparative example 1 (without a catalytic additive), among which the removal rate is the highest when the molar ratio of the reactants is 1.5.
[0117] Example 11 Effect of reducing agent type on polishing rate
[0118] This example is basically the same as Example 1, the only difference is the type of reducing agent in step S1. In Example 1, step 1 uses ethanol. In this example, the polishing rate under equimolar amounts of methanol, propanol, isopropanol, sec-butyl alcohol, formaldehyde, formic acid, and acetic acid are tested respectively. The composition and polishing conditions of the prepared polishing liquid are the same as those of Example 1. The polishing results with different reducing agents are shown in Table 11:
[0119] Table 11 Effect of reducing agent type on polishing rate
[0120] reducing agent MRR Methanol 1.10 μm / h Ethanol 1.30 μm / h Propanol 1.20 μm / h Isopropyl alcohol 1.16 μm / h Sec-Butanol 1.08 μm / h formaldehyde 0.98 μm / h Formic acid 1.13 μm / h Acetic acid 1.05 μm / h
[0121] It can be seen from the results in Table 11 that when the reducing agent is different, the polishing rate is improved to a certain extent compared with the comparative example 1 (without catalytic aid), among which the removal rate is the highest when the reducing agent is ethanol.
[0122] Example 12 Effect of pH of polishing liquid on polishing rate
[0123] This example is basically the same as Example 1, the only difference is the pH of the polishing liquid in the preparation of the chemical mechanical polishing liquid. The pH of the polishing liquid in Example 1 is 8.5, and this example tests the polishing rate at pH 2, 4, and 10 of the polishing liquid. The composition and polishing conditions of the prepared polishing liquid are the same as those in Example 1. The polishing results of the polishing liquid at different pH are shown in Table 12:
[0124] Table 12 Effect of pH of polishing liquid on polishing rate
[0125] pH of polishing liquid MRR 2.0 0.74 μm / h 4.0 0.99 μm / h 8.5 1.30 μm / h 10.0 1.20 μm / h
[0126] It can be seen from the results in Table 12 that when the pH value of the polishing liquid is different, the polishing rate is improved to a certain extent compared with the comparative example 1 (without catalyst auxiliary agent), among which the removal rate is the highest when the pH value of the polishing liquid is 8.5.
[0127] Example 13 Effect of Flower-Shaped δ-MnO2 Nanoparticle Concentration on Polishing Rate
[0128] This example is basically the same as Example 1, the only difference is the concentration of the flower-shaped δ-MnO2 nanoparticles in the chemical mechanical polishing solution. The concentration of the flower-shaped δ-MnO2 nanoparticles in Example 1 is 1.0 wt%. This example tests the polishing rate at concentrations of 0.5 wt%, 1.5 wt%, and 2.0 wt%, respectively. The composition and polishing conditions of the prepared polishing solution are the same as those in Example 1. The polishing results at different catalyst concentrations in the polishing solution are shown in Table 13:
[0129] Table 13 Effect of flower-shaped δ-MnO2 nanoparticle concentration on polishing rate
[0130] δ-MnO2 concentration MRR 0.5 wt% 1.15 μm / h 1.0 wt% 1.18 μm / h 1.5 wt% 1.30 μm / h 2.0 wt% 1.11 μm / h
[0131] It can be seen from the results in Table 13 that when the concentration of flower-shaped δ-MnO2 nanoparticles is different, the polishing rate is improved to a certain extent compared with the comparative example 1 (without catalyst), among which the removal rate is the highest when the concentration of flower-shaped δ-MnO2 nanoparticles is 1.5 wt%.
[0132] Example 14 Effect of post-treatment method on polishing rate
[0133] This example is basically the same as Example 1, the only difference is the post-treatment step of the flower-shaped δ-MnO2 nanoparticles. In Example 1, the flower-shaped δ-MnO2 nanoparticles are used directly after preparation to prepare the chemical mechanical polishing liquid, while in this example, the prepared flower-shaped δ-MnO2 nanoparticles are filtered and dried to constant weight, and then redistributed into the polishing liquid for use. The composition and polishing conditions of the prepared polishing liquid are the same as those of Example 1. The polishing results of different post-treatment methods are shown in Table 15:
[0134] Table 14 Effect of post-treatment method on polishing rate
[0135] Post-processing method MRR Direct use 1.30 μm / h Use after filtering and drying 1.17 μm / h
[0136] It can be seen from the results in Table 14 that, when the post-treatment methods are different, the polishing rate is improved to a certain extent compared with the comparative example 1 (without catalyst additive), among which the removal rate is the highest when the post-treatment method is used directly.
[0137] Example 15 Comparison with commercially available δ-MnO2 catalyst
[0138] This example is basically the same as Example 1, the only difference being that a commercially available nano-δ-MnO2 catalyst is used. The commercially available nano-δ-MnO2 catalyst is provided by Dalian Tongmanganese New Material Technology Co., Ltd., and its parameter specifications are shown in Table 15 below:
[0139] Table 15 Specifications of commercially available nano-δ-MnO2 nanoparticle catalysts
[0140]
[0141] The composition of the prepared polishing liquid and the polishing conditions are the same as those in Example 1. The polishing results of different catalysts are shown in Table 16:
[0142] Table 16 Comparison with commercially available nano δ-MnO2 nanoparticle catalysts
[0143] <![CDATA[δ-MnO2 concentration]]> Catalyst MRR of this example Commercially available catalyst MRR 0.5 wt% 1.15 μm / h 0.97 μm / h 1.0 wt% 1.18 μm / h 0.99 μm / h 1.5 wt% 1.30 μm / h 1.02 μm / h 2.0 wt% 1.11 μm / h 0.98 μm / h
[0144] It can be clearly seen from Table 16 that the commercially available δ-MnO2 catalyst has only a small increase in the polishing rate, from 0.96 μm / h without catalyst to 1.02 μm / h, an increase of only 6%, which is comparable to the performance of the commercially available γ-MnO2 catalyst. Under the same conditions, the catalyst synthesized in this embodiment has a polishing rate of 1.30 μm / h, an increase of 35%. This shows that the δ-MnO2 catalyst synthesized in this embodiment has a higher catalytic activity than the commercially available δ-MnO2 catalyst, which is inseparable from the unique physicochemical properties of the δ-MnO2 catalyst in this embodiment, namely, high specific surface area and rich pore structure, rich active sites and oxygen vacancies, ultra-thin sheet structure, etc. These physicochemical properties have a great promoting effect on the catalytic activity.
[0145] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A chemical mechanical polishing liquid, characterized in that: Includes the following components: 1.5 wt % of flower-shaped δ-MnO2 nanoparticles, 2.0 wt % of α-alumina abrasive particles, 2.0 wt % of potassium permanganate oxidant, and a pH adjuster in an amount such that the pH value of the chemical mechanical polishing solution reaches 8.5; The flower-shaped δ-MnO2 nanoparticles are prepared by the following method: S1, using an organic compound as a reducing agent and dissolving it in deionized water to obtain solution A; S2, dissolving permanganate in deionized water to obtain solution B; S3, mixing solution A and solution B, reacting to obtain flower-shaped δ-MnO2 nanoparticles; In step S3, the reaction time is 0.02-48 h, the reaction temperature is 20° C.-100° C., and the reaction pH value is 1.0-14.0; The organic compound is ethanol, and the permanganate is selected from potassium permanganate; The molar concentration of the organic compound in solution A is 0.01~18.0 mol / L, and the molar concentration of the permanganate in solution B is 0.01~2.0 mol / L; In step S3, solution A and solution B are added in a molar ratio of organic compound to permanganate of 0.2 to 5.0:
1.
2. The chemical mechanical polishing solution according to claim 1, characterized in that: The organic compound in solution A is ethanol, with a concentration of 2.84 mol / L; the permanganate in solution B is potassium permanganate, with a concentration of 0.40 mol / L; In step S3, solution A and solution B are added in a molar ratio of organic compound to permanganate of 1.5:1; The reaction time in step S3 is 24 h, the reaction temperature is 20° C., and the reaction pH is 10.
3. The chemical mechanical polishing solution according to claim 1, characterized in that: The pH regulator is selected from one or more of phosphoric acid, hydrogen phosphate, nitric acid, sulfuric acid, potassium hydroxide, sodium hydroxide, triethanolamine, oxalic acid, and amino acids.
Citation Information
Patent Citations
Polishing method adopting in-situ feeding and application
CN116061080A
Cited By
Method and apparatus for closed-loop control of silicon carbide wafer polishing process based on online monitoring
CN122559869A